THE CONCEPT OF "TIME" IN THE RUSSIAN LINGUISTIC WORLDVIEW: LEXICAL REPRESENTATION AND CULTURAL CONNOTATIONS - Dilshod Khamraev (International Journal of Literature and Language Studies, 2026)
:This article examines the concept "time" in the Russian linguistic worldview through the analysis of its lexical field, conceptual metaphors, phraseological units, and proverbs. Drawing on data from Russian explanatory dictionaries, the Russian National Corpus, and collections of phraseology and proverbs, the study identifies four core semantic groups within the Russian temporal lexicon and describes three dominant metaphorical models: time as a resource, time as a moving entity, and time as a moral agent. Cultural connotations encoded in phraseological units and proverbs reveal a nationally specific duality between the instrumental and contemplative orientations toward time. The results contribute to the linguocultural study of temporal concepts and to comparative research on the Russian linguistic worldview.